Positive electrode active material, positive electrode, and lithium secondary battery comprising the same

By using molten salt-based fluid and metal oxide-based toner during the sintering of lithium composite oxides, uniform particle size growth is induced, and the problems of uneven particle size distribution and high processing cost of single-crystal positive electrode active material in the prior art are solved, thereby achieving efficient improvement in the performance of lithium-ion secondary batteries.

JP2025071011AActive Publication Date: 2025-05-02ECOPRO BM CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024180439
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-10-19
Filing Date
2024-10-16
Publication Date
2025-05-02
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

The prior art is difficult to achieve uniform particle size distribution and high particle size distribution sharpness of the positive electrode active material of single crystal lithium composite oxide without using strict sintering conditions and decomposition steps, resulting in an increase in aggregation phenomenon and processing costs.

Method used

The molten salt-based fluid and metal oxide-based toner are used to induce uniform particle size growth during the sintering stage of the lithium composite oxide precursor, and the strict sintering conditions and decomposition steps are avoided.

Benefits of technology

The uniform particle size distribution and high particle size distribution sharpness of the positive electrode active material are achieved, which reduces aggregation phenomenon and processing costs, and at the same time improves the capacity and life characteristics of lithium-ion secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025071011000001_ABST
    Figure 2025071011000001_ABST
Patent Text Reader

Abstract

To provide a single-crystal type positive electrode active material which can exhibit relatively high battery performance and can have a uniform particle size distribution by inducing uniform particle growth even without any harsh calcination condition or disintegration process and by reducing inter-particle agglomeration.SOLUTION: A positive electrode active material comprises a lithium composite oxide capable of intercalation / deintercalation of lithium, where the lithium composite oxide includes at least lithium and transition metal and has D10, D50, D90 and Dmax satisfying all of Formulas 1 to 3 in the following: D90 / D10≤3.62 [Formula 1]; Dmax-D90<2.0 μm [Formula 2]; and Dmax / Dmin<5.19 [Formula 3].SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode active material and a lithium secondary battery including the same, and more specifically, to a single crystal type positive electrode active material having a uniform particle size distribution and high sharpness of the particle size distribution, a positive electrode, and a lithium secondary battery including the same. [Background technology]

[0002] Batteries store electricity by using materials capable of electrochemical reactions at the positive and negative electrodes. A representative example of such batteries is a lithium secondary battery, which stores electrical energy by the difference in chemical potential when lithium ions are intercalated / deintercalated at the positive and negative electrodes.

[0003] The lithium secondary battery is manufactured by using a material capable of reversible intercalation / deintercalation of lithium ions as a positive electrode and a negative electrode active material, and filling an organic electrolyte or a polymer electrolyte between the positive electrode and the negative electrode.

[0004] Lithium composite oxides are used as the positive electrode active material in lithium secondary batteries, and examples of these include LiCoO 2 , LiMn 2 O 4 , LiNiO 2 , LiMnO 2 Composite oxides such as these are being researched.

[0005] Among the positive electrode active materials, LiCoO 2 is the most widely used due to its excellent life characteristics and charge / discharge efficiency, but has the disadvantage that its price competitiveness is limited because the cobalt used as a raw material is expensive.

[0006] LiMnO 2 , LiMn 2 O 4Lithium manganese oxides such as LiNiO have the advantages of being thermally safe and inexpensive, but they have problems such as small capacity and poor high-temperature properties. 2 Although the positive electrode active material based on this system has the advantage of exhibiting a high discharge capacity, it is difficult to synthesize due to active cation mixing of Li and Ni, and the rate characteristic and life characteristic of the synthesized positive electrode active material are very poor.

[0007] This resulted in LiNiO 2 In order to improve the low rate and life characteristics while maintaining the high reversible capacity of lithium composite oxides, ternary type lithium composite oxides such as NCM (Ni-Co-Mn) and NCA (Ni-Co-Al) or quaternary type lithium composite oxides such as NCMA (Ni-Co-Mn-Al) have been developed in which part of the nickel is replaced with cobalt, manganese and / or aluminum. The lower the nickel content in such ternary or quaternary type lithium composite oxides, the lower the reversible capacity, so recently, active research has been conducted to increase the nickel content in lithium composite oxides.

[0008] In addition, general ternary or quaternary type lithium composite oxides have the form of secondary particles in which tens to hundreds or more primary particles are aggregated, but it has been reported that the stability (life characteristics, etc.) of the positive electrode active material can be improved as the number of primary particles constituting the secondary particles is reduced. Such lithium composite oxides with a reduced number of primary particles are also called lithium composite oxides with a single crystal structure or lithium composite oxides with a single particle structure.

[0009] For example, Non-Patent Document 1 describes a lithium composite oxide (LiNi 0.5 Mn 0.3 Co 0.2 O 2 It is disclosed that the stability of the lithium composite oxide having the same composition as that of a polycrystalline structure is partially improved.

[0010] However, as disclosed in Non-Patent Document 1, when the firing temperature is excessively increased or the amount of lithium relative to the transition metal in the lithium composite oxide is excessively increased in order to form a single crystal of the lithium composite oxide constituting the positive electrode active material, the phenomenon of cation mixing may increase in the crystal structure.

[0011] In particular, when the cation mixing phenomenon increases in a lithium composite oxide having a single crystal structure, a phase other than the layered crystal structure (e.g., a rock-salt phase) is formed, which can change the surface resistance characteristics of the lithium composite oxide or cause early deterioration.

[0012] In addition, when the lithium composite oxide is induced to be a single crystal by simply subjecting it to harsh sintering conditions (e.g., over-sintering at a high sintering temperature), it is difficult to induce uniform particle growth, and agglomeration between particles occurs, making it impossible to obtain a positive electrode active material having a uniform particle size distribution.

[0013] In addition, a positive electrode active material including a lithium composite oxide having a single crystal structure can be manufactured by synthesizing secondary particles in which a plurality of primary particles are aggregated, and then performing a crushing process. However, the crushing process not only has a problem of a sharp increase in the processing cost of the positive electrode active material, but also has a risk of causing damage to the surface of the lithium composite oxide during the crushing process. The defects present on the surface of the lithium composite oxide can change the surface resistance characteristics of the lithium composite oxide. In addition, the surface defects can cause a side reaction with the electrolyte to generate gas, and cracks can occur along the surface defects.

[0014] Therefore, there is a need for the development of a single-crystal type positive electrode active material that can reduce the aggregation phenomenon between particles by inducing uniform particle growth and has a uniform particle size distribution without a separate crushing process after firing the precursor. [Prior art documents] [Patent documents]

[0015] [Non-Patent Document 1] Journal of the Electrochemical Society, Volume 164, Number 7, A1534-A1544 (Published 2017.05.23) Summary of the Invention [Problem to be solved by the invention]

[0016] In the lithium secondary battery market, the growth of lithium secondary batteries for electric vehicles is playing a leading role in the market, and as a result, the demand for positive electrode active materials used in lithium secondary batteries is also continuously increasing.

[0017] For example, lithium secondary batteries using lithium iron phosphate (LFP) have been mainly used in the past due to safety concerns, but recently there has been a trend towards the use of nickel-based lithium composite oxides, which have a higher energy capacity per weight than LFP. Of course, relatively cheap LFP is still sometimes used to save costs.

[0018] Recently, nickel-based lithium composite oxides that are mainly used as positive electrode active materials for high-capacity lithium secondary batteries generally have a ternary type composition such as NCM (Ni-Co-Mn) and NCA (Ni-Co-Al) or a quaternary type composition such as NCMA (Ni-Co-Mn-Al).

[0019] As described above, in order to realize high capacity of such ternary or quaternary type nickel-lithium composite oxides, the stability (life characteristics, etc.) of the positive electrode active material can be improved by reducing the number of primary particles constituting the secondary particles.

[0020] However, in the processes that have been commercialized so far, the crystal structure of the lithium composite oxide may change due to the harsh sintering conditions, and since uniform particle growth is difficult to induce under the harsh sintering conditions, a crushing process is required, which leads to a problem of a sharp increase in the processing cost of the positive electrode active material.

[0021] Therefore, an object of the present invention is to provide a single crystal type positive electrode active material that can have a uniform particle size distribution by inducing uniform particle growth without harsh firing conditions and a crushing process, thereby reducing the aggregation phenomenon between particles, and can exhibit relatively high battery performance.

[0022] Another object of the present invention is to provide a positive electrode active material having a sharp particle size distribution due to uniform particle growth and reduced aggregation between particles.

[0023] Another object of the present invention is to provide a lithium secondary battery using the positive electrode active material defined herein.

[0024] The object of the present invention is not limited to the object mentioned above, and other objects and advantages of the present invention not mentioned can be understood from the following description and will be more clearly understood by the embodiments of the present invention. In addition, it will be easily known that the object and advantages of the present invention can be realized by the means and combinations thereof as set forth in the claims. [Means for solving the problem]

[0025] According to one aspect of the present invention, there is provided a positive electrode active material including a lithium composite oxide capable of lithium intercalation / deintercalation, the lithium composite oxide satisfying all of the following formulas 1 to 3.

[0026] [Formula 1] D 90 / D 10 ≦3.62 [Formula 2] D max -D 90 <2.0μm [Formula 3] D max / D min <5.19 (In the above formulas 1 to 3, the D 10 is the particle size of the lithium composite oxide at which the volume cumulative amount is 10% in a volume cumulative particle size distribution graph obtained by laser diffraction particle size distribution measurement, and 50 is the particle size of the lithium composite oxide at which the volume cumulative amount is 50% in the volume cumulative particle size distribution graph, and D 90 is the particle size of the lithium composite oxide at which the volume cumulative amount is 90% in the volume cumulative particle size distribution graph, and D min is the minimum particle size of the lithium composite oxide in the volume cumulative particle size distribution graph, and D max is the maximum particle size of the lithium composite oxide in the volume cumulative particle size distribution graph.

[0027] The lithium composite oxide constituting the positive electrode active material according to the above embodiment may be a single crystal type having a uniform particle size distribution and high sharpness of the particle size distribution.

[0028] In the present invention, the D of the lithium composite oxide 50 is preferably 2 μm to 8 μm, and D of the lithium composite oxide max It is preferable that the thickness is 15 μm or less.

[0029] In one embodiment, the lithium composite oxide may satisfy at least one or both of the following formulas 4 and 5:

[0030] [Formula 4] D 50 / D 10 <1.19 [Formula 5] D max -D50 <7.8μm In the present invention, the lithium composite oxide contains at least lithium and a transition metal. In the present invention, the transition metal may contain at least one, at least two, at least three, or all of nickel, cobalt, manganese, and aluminum.

[0031] In the positive electrode active material of the present invention, the lithium composite oxide can be represented by the following chemical formula 1. [Chemical formula 1] Li a Ni 1-(b+c+d) Co b M1 c M2 d O 2 (wherein M1 is at least one selected from Mn and Al, M2 is at least one selected from the group consisting of Na, K, Mg, Ca, Ba, Mn, B, Ce, Hf, Ta, Cr, F, Al, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, Ge, Nd, Gd and Cu, M1 and M2 are different from each other, and 0.5≦a≦1.5, 0≦b≦0.20, 0≦c≦0.30, 0≦d≦0.10.)

[0032] In the present invention, the lithium composite oxide may be present in at least one form selected from a single particle and a secondary particle formed by aggregation of a plurality of primary particles. The secondary particles may be in a state where 1 to 10 primary particles are aggregated.

[0033] According to another aspect of the present invention, there is provided a positive electrode including the above-described positive electrode active material. According to yet another aspect of the present invention, there is provided a lithium secondary battery using the above-mentioned positive electrode. Effect of the Invention

[0034] According to the present invention, a positive electrode active material with reduced aggregation between particles can be obtained by inducing uniform particle growth without harsh firing conditions and a crushing process by using a combination of a molten salt-based flux and a metal oxide-based dopant in the firing step of a precursor.

[0035] The positive electrode active material obtained through this process has the advantage of having a uniform particle size distribution, particularly a high sharpness of the particle size distribution. When a positive electrode active material having such a high sharpness of the particle size distribution is used, the capacity characteristics and life characteristics of a lithium secondary battery can be improved.

[0036] In addition to the above-mentioned advantages, specific advantages of the present invention will be described together with the following description of the preferred embodiments of the present invention. [Brief description of the drawings]

[0037] [Figure 1] 2 is a SEM image of the positive electrode active material according to Example 1. [Diagram 2] 1 is an SEM image of the positive electrode active material according to Example 2. [Diagram 3] 1 is an SEM image of the positive electrode active material according to Example 3. [Figure 4] 1 is an SEM image of the positive electrode active material according to Comparative Example 1. [Diagram 5] 1 is an SEM image of the positive electrode active material according to Comparative Example 2. [Figure 6] 1 is an SEM image of the positive electrode active material according to Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0038] In order to make the present invention easier to understand, certain terms are defined herein for convenience. Unless otherwise defined herein, scientific and technical terms used in the present invention shall have the meanings commonly understood by those of ordinary skill in the art. Furthermore, unless otherwise specified by the context, singular terms shall be understood to include their plural forms, and plural terms shall be understood to include their singular forms.

[0039] positive electrode active material A positive electrode active material according to one embodiment of the present invention is capable of reversible intercalation / deintercalation of lithium ions and includes a lithium composite oxide.

[0040] In the positive electrode active material of the present invention, the lithium composite oxide is preferably a composite metal oxide capable of intercalating / deintercalating lithium ions and has a layered crystal structure belonging to the R-3m space group. The lithium composite oxide having a layered crystal structure preferably exhibits a specific peak in the region of 2θ of 18° to 20° in the rotation pattern obtained by XRD analysis.

[0041] In the positive electrode active material of the present invention, the lithium composite oxide contains at least lithium and a transition metal. The transition metal may contain at least one, at least two, at least three, or all of nickel, cobalt, manganese, and aluminum.

[0042] Preferably, the lithium composite oxide may be a lithium nickel-based composite oxide containing nickel. Also, the lithium composite oxide may be a lithium nickel-based composite oxide containing nickel and cobalt.

[0043] In one embodiment, LiNiO 2In order to improve the low rate characteristics and life characteristics while maintaining the high reversible capacity of the lithium nickel-based composite oxide, the lithium nickel-based composite oxide may be a ternary type such as NCM (Ni-Co-Mn) and NCA (Ni-Co-Al) in which a part of nickel is replaced with cobalt, manganese, and / or aluminum, or a quaternary type such as NCMA (Ni-Co-Mn-Al). The ternary or quaternary type lithium composite oxide may further contain a dopant other than nickel, cobalt, manganese, and aluminum. In another embodiment, the lithium nickel-based composite oxide may be a cobalt-free type lithium composite oxide that does not contain cobalt in the bulk particles. The cobalt-free type lithium composite oxide may further contain a dopant other than nickel, cobalt, manganese, and aluminum.

[0044] In the present invention, the lithium composite oxide is preferably represented by the following chemical formula 1. [Chemical formula 1] Li a Ni 1-(b+c+d) Co b M1 c M2 d O 2 Here, M1 is at least one selected from Mn and Al, and M2 is at least one selected from the group consisting of Na, K, Mg, Ca, Ba, Mn, B, Ce, Hf, Ta, Cr, F, Al, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, Ge, Nd, Gd, and Cu, and M1 and M2 are different from each other and 0.5≦a≦1.5, 0≦b≦0.20, 0≦c≦0.30, and 0≦d≦0.10.

[0045] In the lithium composite oxide, a, which indicates the ratio of lithium to all elements other than lithium (Ni+Co+M1+M2), is preferably 0.5 or more and 1.5 or less, more preferably 0.75 or more and 1.25 or less, even more preferably 0.90 or more and 1.1 or less, and particularly preferably 0.95 or more and 1.05 or less.

[0046] In one embodiment, the lithium composite oxide may be a lithium nickel-based composite oxide in which the molar fraction of nickel relative to all elements other than lithium in the lithium composite oxide is 70% or more. In this case, the positive electrode active material of the present invention is preferably such that b+c+d is 0.30 or less in Chemical Formula 1. That is, the lithium composite oxide according to the embodiment is a lithium nickel-based composite oxide in which the molar fraction of nickel relative to all elements other than lithium is 70% or more and which has a layered crystal structure belonging to the R-3m space group.

[0047] In addition, according to another embodiment, the molar fraction of nickel relative to all elements other than lithium in the lithium composite oxide is more preferably 75% or more (in this case, b+c+d is 0.25 or less), even more preferably 80% or more (in this case, b+c+d is 0.20 or less), even more preferably 85% or more (in this case, b+c+d is 0.15 or less), and particularly preferably 90% or more (in this case, b+c+d is 0.10 or less).

[0048] When the lithium composite oxide contains cobalt, the molar fraction of cobalt relative to all elements other than lithium in the secondary particles is preferably 20% or less, more preferably 15% or less, even more preferably 10% or less, and particularly preferably 5% or less.When the lithium composite oxide contains cobalt, b in Chemical Formula 1 is greater than 0, and when the lithium composite oxide is a cobalt-free type lithium composite oxide that does not contain cobalt, b in Chemical Formula 1 is 0.

[0049] When the lithium composite oxide contains manganese and / or aluminum, the molar fraction of manganese and / or aluminum relative to the total elements other than lithium in the lithium composite oxide is preferably 30% or less, more preferably 20% or less, even more preferably 15% or less, even more preferably 10% or less, and particularly preferably 5% or less. When the lithium composite oxide contains manganese and / or aluminum, c in Chemical Formula 1 is greater than 0.

[0050] In the formula 1, M2 refers to a dopant present in the secondary particles. The dopant may be present in a doped state in the crystal lattice of the primary particles. Also, in the formula 1, M2 may selectively include an element derived from a molten salt-based flux and / or a metal oxide-based dopant used in the step of calcining the lithium composite oxide precursor.

[0051] When the lithium composite oxide contains a dopant, d in the above Chemical Formula 1 is greater than 0, and when the lithium composite oxide does not contain a dopant, d in the above Chemical Formula 1 is 0.

[0052] In addition, the content of the dopant relative to all elements other than lithium in the secondary particles is smaller than the contents of nickel, cobalt, and M1. For example, the molar fraction of the dopant relative to all elements other than lithium in the secondary particles is preferably 10% or less, more preferably 5% or less, more preferably 4% or less, more preferably 3% or less, more preferably 2% or less, more preferably 1% or less, more preferably 0.5% or less, more preferably 0.4% or less, more preferably 0.3% or less, more preferably 0.2% or less, and particularly preferably 0.1% or less.

[0053] When the secondary particles selectively contain a dopant, the dopant may include at least one selected from the group consisting of Na, K, Mg, Ca, Ba, Mn, B, Ce, Hf, Ta, Cr, F, Al, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, Ge, Nd, Gd and Cu.

[0054] The upper and lower limits of the contents of nickel, cobalt, M1 and M2 defined in the above Chemical Formula 1 may be appropriately selected within the ranges satisfying the above definitions.

[0055] In the positive electrode active material of the present invention, the lithium composite oxide may be present in at least one form selected from single particles and secondary particles in which a plurality of primary particles are aggregated. Thus, the positive electrode active material may be present as an aggregate of single particles and secondary particles. However, if the aggregation phenomenon between particles is reduced by inducing uniform particle growth during the manufacturing process of the positive electrode active material, a positive electrode active material having a more uniform particle size distribution and particularly a high sharpness of the particle size distribution can be obtained as the ratio of single particles to secondary particles in the aggregate increases. When a positive electrode active material having such a sharp particle size distribution is used, the capacity characteristics and life characteristics of a lithium secondary battery can be improved. Here, a narrow width of the peak of the particle size distribution confirmed from the volume cumulative particle size distribution graph may mean that the sharpness of the particle size distribution is high.

[0056] When the single particles are aggregated and exist as secondary particles, each single particle constituting the secondary particle may be referred to as a primary particle. In this case, the compositions of the single particles, the primary particles, and the secondary particles may all be represented by the above-mentioned Chemical Formula 1. In addition, the single particles, the primary particles, and the secondary particles all exist as particles capable of lithium intercalation / deintercalation.

[0057] The single particles and the primary particles may have a rod shape, an elliptical shape, and / or an irregular shape. Furthermore, primary particles of various shapes may be present in the same positive electrode active material unless otherwise intended in the manufacturing process. Furthermore, the primary particles refer to particle units that do not have grain boundaries in appearance when observed at a magnification of 5,000 to 20,000 times using a scanning electron microscope.

[0058] The average particle size of the single particles and the average particle size of the primary particles are preferably 0.5 μm to 10 μm, more preferably 0.5 μm to 8 μm, more preferably 0.5 μm to 6 μm, more preferably 0.5 μm to 5 μm, more preferably 1 μm to 10 μm, more preferably 1 μm to 8 μm, more preferably 1 μm to 6 μm, more preferably 1 μm to 5 μm, more preferably 2 μm to 10 μm, more preferably 2 μm to 8 μm, more preferably 2 μm to 6 μm, or particularly preferably 2 μm to 5 μm. In this case, the average particle size of the single particles and the primary particles can be the average value of the length in the major axis direction and the length in the minor axis direction of the single particles and the primary particles ([major axis length + minor axis length] / 2).

[0059] The lithium composite oxide is a single crystal type lithium composite oxide, where the single crystal type means that a single particle or a primary particle, which is the minimum particle unit constituting the lithium composite oxide, exists as a single crystallite.

[0060] When secondary particles are present in the aggregate, the average particle size of the secondary particles is preferably 0.5 μm to 15 μm, more preferably 1.0 μm to 12 μm, even more preferably 1.0 μm to 10 μm, even more preferably 2.0 μm to 12 μm, and particularly preferably 2.0 μm to 10 μm. Here, the average particle size of the secondary particles can be calculated as the average particle size of the secondary particles confirmed from a SEM image. The average particle size of the secondary particles can vary depending on the number of the primary particles constituting the secondary particles.

[0061] The particle size distribution of the lithium composite oxide in the positive electrode active material can be measured using a laser diffraction method. For example, the secondary particles are dispersed in a dispersion medium, then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000), and irradiated with ultrasonic waves of about 28 kHz at an output of 60 W. Then, a volume cumulative particle size distribution graph is obtained, and the particle sizes corresponding to volume cumulative amounts of 10%, 50%, and 90%, the minimum particle size in the volume cumulative particle size distribution graph, and the maximum particle size in the volume cumulative particle size distribution graph can be calculated.

[0062] Here, the particle size of the lithium composite oxide (single particles or secondary particles) corresponding to 50% of the cumulative volume is defined as the average particle size (D 50 ) is defined as D 10 is a particle size of the lithium composite oxide (single particle or secondary particle) at which the volume cumulative amount is 10% in a volume cumulative particle size distribution graph obtained by laser diffraction particle size distribution measurement, and D 50 is a particle size of the lithium composite oxide (single particle or secondary particle) at which the volume cumulative amount is 50% in the volume cumulative particle size distribution graph, and D 90 is the particle size of the lithium composite oxide (single particle or secondary particle) at which the volume cumulative amount is 90% in the volume cumulative particle size distribution graph, and D minis the minimum particle size of the lithium composite oxide (single particle or secondary particle) in the volume cumulative particle size distribution graph, and D max is defined as the maximum particle size of the lithium composite oxide (single particle or secondary particle) in the volume cumulative particle size distribution graph.

[0063] In one embodiment, the lithium composite oxide D 50 is preferably 2 μm to 8 μm, more preferably 3 μm to 7 μm, and further preferably 4 μm to 6 μm, and D of the lithium composite oxide is max is preferably 15 μm or less, more preferably 14 μm or less, and even more preferably 13 μm or less.

[0064] In addition, D of the lithium composite oxide min is preferably 0.5 μm to 4 μm, more preferably 1 μm to 4 μm, and further preferably 2 μm to 3.2 μm; D 10 is preferably 1 μm to 4 μm, more preferably 2 μm to 4 μm, and further preferably 2.5 μm to 3.5 μm; D 90 The thickness is preferably 6 μm to 15 μm, more preferably 8 μm to 12 μm, and further preferably 9 μm to 12 μm.

[0065] D as defined above min , D 10 , D 50 , D 90 and D. max The upper and lower limits can be appropriately selected within a range satisfying the following formulae 1 to 3, formulae 1 to 4, formulae 1 to 3 and 5, or formulae 1 to 5. The following formulas 1 to 5 are calculated based on an aggregate including single particles and secondary particles.

[0066] In the present invention, the lithium composite oxide is D 10 and D 90 and satisfy the following formula 1. [Formula 1] D 90 / D 10 ≦3.62 D 90 / D 10 When the value of β-axis direction is 3.62 or less, the deviation in particle size between the lithium composite oxide having a relatively small particle size and the lithium composite oxide having a relatively large particle size among the positive electrode active materials can be reduced. D 90 / D 10 may be within the range of 3.3 to 3.8, 3.3 to 3.7, 3.4 to 3.65, 3.42 to 3.62, or 3.45 to 3.62.

[0067] In the positive electrode active material of the present invention, the lithium composite oxide is 90 and D max and satisfy the following formula 2. [Formula 2] D max -D 90 <2.0μm D max -D 90 means the difference between the maximum particle size in the aggregate and the particle size that is 90% of the cumulative volume, and D max -D 90 A particle size distribution of less than 2.0 μm means that the sharpness of the particle size distribution is high. D max -D 90 is less than 2.0 μm, preferably 1.9 μm or less, and more preferably 1.8 μm or less. In order to ensure an appropriate sharpness of the particle size distribution, D max -D 90 is preferably 0.75 μm, and more preferably greater than 1 μm.

[0068] In the positive electrode active material of the present invention, the lithium composite oxide is min and D max and satisfy the following formula 3. [Formula 3] D max / D min <5.19 D max / D min is the ratio of the maximum particle size to the minimum particle size in the aggregate, and D max / D min As the value of β increases, the deviation between the minimum particle size and the maximum particle size in the aggregate increases, so that the uniformity of the particle size distribution decreases and the sharpness of the particle size distribution decreases.

[0069] D max / D min is less than 5.19, preferably 5.1 or less, more preferably 5.0 or less, even more preferably 4.95 or less, and particularly preferably 4.92 or less. In order to ensure an appropriate sharpness of the particle size distribution, D max / D min is preferably greater than 2 or 3.

[0070] According to the present invention, a molten salt-based flux and a metal oxide-based dopant are used in combination in the firing step of the lithium composite oxide precursor, thereby inducing uniform particle growth without harsh firing conditions and a crushing process, thereby making it possible to obtain a positive electrode active material with reduced aggregation between particles.

[0071] The positive electrode active material obtained through this process has the advantage of having a uniform particle size distribution, particularly a high sharpness of the particle size distribution. When a positive electrode active material having such a high sharpness of the particle size distribution is used, the capacity characteristics and life characteristics of a lithium secondary battery can be improved.

[0072] In this way, a positive electrode active material having a uniform particle size distribution and high sharpness of the particle size distribution preferably satisfies all of formulas 1 to 3.

[0073] In the present invention, in order to further improve the uniformity and sharpness of the particle size distribution of the lithium composite oxide in the positive electrode active material, the lithium composite oxide is10 and D 50 and D max can satisfy at least one or both of the following formulas 4 and 5.

[0074] [Formula 4] D 50 / D 10 <1.19

[0075] D 50 / D 10 is the ratio of the particle size (average particle size) that is 50% of the cumulative volume in the aggregate to the particle size that is 10% of the cumulative volume, and D 50 / D 10 The larger the value, the closer the D is to the average particle size and the minimum particle size in the volume cumulative particle size distribution graph. 10 Since the deviation between the particle size distribution and the particle size distribution is large, the uniformity of the particle size distribution decreases and the sharpness of the particle size distribution decreases.

[0076] D 50 / D 10 is preferably less than 1.19, more preferably 1.18 or less, even more preferably 1.17 or less, and particularly preferably 1.16 or less. In order to ensure an appropriate sharpness of the particle size distribution, D 50 / D 10 is preferably greater than 1.

[0077] [Formula 5] D max -D 50 <7.8μm

[0078] D max -D 50 means the difference between the maximum particle size in the aggregate and the particle size (average particle size) that is 50% of the cumulative volume, and D max -D 90 Similarly, the above D max -D 50 By having a value of less than 7.8 μm, the sharpness of the particle size distribution can be improved.

[0079] D max -D 50 is preferably less than 7.8 μm, more preferably 7.6 μm or less, even more preferably 7.4 μm or less, and particularly preferably 7.2 μm or less. In order to ensure an appropriate sharpness of the particle size distribution, D max -D 50 is preferably greater than 3 μm, more preferably greater than 4 μm.

[0080] As described above, the lithium composite oxide may be present in at least one form selected from a single particle and a secondary particle formed by agglomeration of a plurality of primary particles, and the positive electrode active material may be present as an aggregate of the single particle and the secondary particle. That is, the positive electrode active material can be defined as an aggregate of a plurality of lithium composite oxides having the same and / or different grain boundary densities.

[0081] The grain boundary density can be calculated by substituting the number of primary particles (P) placed on a virtual straight line (L) that crosses the center of the lithium composite oxide in the long axis direction in a cross-sectional SEM image of the lithium composite oxide into the following formula 6.

[0082] [Formula 6] Grain boundary density = (number of boundaries (B) between primary particles placed on the imaginary straight line (L) / number of primary particles (P) placed on the imaginary straight line (L))

[0083] For example, when the lithium composite oxide is a single particle, the number of boundaries (grain boundaries) between primary particles placed on the imaginary line is 0, and therefore the grain boundary density has a value of 0. On the other hand, when the number of primary particles (P) placed on the imaginary line (L) is 2 and the number of boundaries (B) between primary particles placed on the imaginary line (L) is 1, the grain boundary density has a value of 0.5.

[0084] The closer the average grain boundary density of the lithium composite oxide present in the aggregate is to 0, the higher the ratio of the lithium composite oxide present as single particles relative to secondary particles in the aggregate.

[0085] In the present invention, the lithium composite oxide present as secondary particles in the aggregate is preferably in a state where 2 to 100 primary particles are aggregated, more preferably in a state where 2 to 50 primary particles are aggregated, even more preferably in a state where 2 to 30 primary particles are aggregated, even more preferably in a state where 2 to 20 primary particles are aggregated, and particularly preferably in a state where 2 to 10 primary particles are aggregated.

[0086] Lithium secondary battery The lithium secondary battery of the present invention uses the positive electrode of the present invention. According to another aspect of the present invention, a positive electrode may be provided, the positive electrode including a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector. Here, the positive electrode active material layer may include a positive electrode active material according to various embodiments of the present invention. Therefore, since the positive electrode active material is the same as that described above, detailed description will be omitted for convenience, and only the remaining components not described above will be described below.

[0087] The positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and may be, for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The positive electrode current collector may usually have a thickness of 3 to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesive strength of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0088] The positive electrode active material layer may be prepared by coating a positive electrode slurry composition containing the positive electrode active material, a conductive material, and optionally a binder, on the positive electrode current collector.

[0089] At this time, the positive electrode active material may be included in a content of 80 wt% to 99 wt%, more specifically, 85 wt% to 98.5 wt%, based on the total weight of the positive electrode active material layer, and excellent capacity characteristics can be exhibited when the content is within this range, but is not necessarily limited thereto.

[0090] The conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it has electronic conductivity without causing chemical changes in the battery that is constructed. Specific examples include graphite such as natural graphite and artificial graphite, carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, carbon-based materials such as carbon fibers, metal powders or metal fibers such as copper, nickel, aluminum, and silver, conductive whiskers such as zinc oxide and potassium titanate, conductive metal oxides such as titanium oxide, and conductive polymers such as polyphenylene derivatives, and the like, and one or more of these may be used alone or in combination. The conductive material may be contained in an amount of 0.1 wt% to 15 wt% based on the total weight of the positive electrode active material layer.

[0091] The binder serves to improve the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, and various copolymers thereof, and among these, one type alone or a mixture of two or more types may be used. The binder may be included in an amount of 0.1 to 15 wt% based on the total weight of the positive electrode active material layer.

[0092] The positive electrode of the present invention includes the positive electrode active material of the present invention. The positive electrode may be manufactured by a conventional method for manufacturing a positive electrode, except for using the positive electrode active material. Specifically, the positive electrode may be manufactured by applying a positive electrode slurry composition prepared by dissolving or dispersing the positive electrode active material and, optionally, a binder and a conductive material in a solvent onto a positive electrode current collector, followed by drying and rolling.

[0093] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and one or more of these may be used alone or in combination. The amount of the solvent used is sufficient to dissolve or disperse the positive electrode active material, conductive material, and binder, and to provide a viscosity that allows excellent thickness uniformity when applied to manufacture a positive electrode, taking into consideration the coating thickness of the slurry and the production yield.

[0094] In another embodiment, the positive electrode may be manufactured by casting the positive electrode slurry composition on a separate support, peeling the positive electrode slurry composition from the support, and laminating the resulting film on a positive electrode current collector.

[0095] According to yet another aspect of the present invention, there may be provided an electrochemical device including the above-mentioned positive electrode. The electrochemical device may be, for example, a battery or a capacitor, and more specifically, a lithium secondary battery.

[0096] Specifically, the lithium secondary battery may include a positive electrode, a negative electrode facing the positive electrode, and a separator and an electrolyte interposed between the positive electrode and the negative electrode. Here, since the positive electrode is as described above, a detailed description thereof will be omitted for convenience, and only the remaining components not described above will be described in detail below.

[0097] The lithium secondary battery may optionally further include a battery container that houses an electrode assembly of the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container. The negative electrode may include a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0098] The negative electrode current collector is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may generally have a thickness of 3 μm to 500 μm, and like the positive electrode current collector, the surface of the current collector may be formed with fine irregularities to strengthen the binding force of the negative electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, or nonwoven fabric.

[0099] The negative electrode active material layer may be prepared by coating a negative electrode slurry composition containing the negative electrode active material, a conductive material, and optionally a binder, on the negative electrode current collector.

[0100] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon, metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys, and SiO β (0<β<2), SnO 2 , a metal oxide capable of doping and dedoping lithium, such as vanadium oxide or lithium vanadium oxide, or a composite containing the metallic compound and a carbonaceous material, such as a Si-C composite or a Sn-C composite, may be used. Any one or a mixture of two or more of these may be used. A thin film of metallic lithium may be used as the negative electrode active material. In addition, both low-crystalline carbon and high-crystalline carbon may be used as the carbon material. Representative examples of low-crystalline carbon include soft carbon and hard carbon, and representative examples of high-crystalline carbon include amorphous, plate-like, scaly, spherical or fibrous natural graphite or artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, carbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes. The negative electrode active material may be included in an amount of 80 wt % to 99 wt % based on the total weight of the negative electrode active material layer.

[0101] The binder is a component that aids in bonding between the conductive material, the active material, and the current collector, and may be added in an amount of 0.1 wt% to 10 wt% based on the total weight of the negative electrode active material layer. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile-butadiene rubber, fluororubber, and various copolymers thereof.

[0102] The conductive material may be added as a component for further improving the conductivity of the negative electrode active material in an amount of 10 wt% or less, preferably 5 wt% or less, based on the total weight of the negative electrode active material layer. Such a conductive material is not particularly limited as long as it has conductivity without inducing a chemical change in the battery, and may be, for example, graphite such as natural graphite or artificial graphite, carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, or thermal black, conductive fibers such as carbon fibers or metal fibers, metal powders such as carbon fluoride, aluminum, or nickel powder, conductive whiskers such as zinc oxide or potassium titanate, conductive metal oxides such as titanium oxide, or conductive materials such as polyphenylene derivatives.

[0103] In one embodiment, the negative electrode active material layer may be prepared by coating a negative electrode slurry composition prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent on a negative electrode current collector and drying the coating. Alternatively, the negative electrode slurry composition may be cast on a separate support, and then peeled off from the support to obtain a film, which may be laminated on the negative electrode current collector.

[0104] In another embodiment, the negative electrode active material layer may be manufactured by coating a negative electrode slurry composition prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent on a negative electrode current collector and drying the coating, or by casting the negative electrode slurry composition on a separate support and peeling the composition from the support to obtain a film, which may be laminated on the negative electrode current collector.

[0105] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode to provide a path for lithium ions to move. Any separator that is generally used as a separator in a lithium secondary battery may be used without any particular limitation. In particular, it is preferable that the separator has low resistance to ion movement of the electrolyte and has excellent electrolyte humidification ability. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting point glass fiber, polyethylene terephthalate fiber, etc. may be used. In addition, in order to ensure heat resistance or mechanical strength, a coated separator containing a ceramic component or a polymer material may be used, and may be selectively used as a single layer or multilayer structure.

[0106] In addition, examples of the electrolyte used in the present application include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the production of lithium secondary batteries, but are not limited to these. Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0107] The organic solvent may be used without any particular limitation as long as it serves as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent may be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, or ε-caprolactone, an ether solvent such as dibutyl ether or tetrahydrofuran, a ketone solvent such as cyclohexanone, an aromatic hydrocarbon solvent such as benzene or fluorobenzene, dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), or propylene carbonate (propylene carbonate). Examples of the solvents that may be used include carbonate-based solvents such as ethylene carbonate (PC), alcohol-based solvents such as ethyl alcohol and isopropyl alcohol, nitriles such as R-CN (R is a straight-chain, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, and sulfolanes. Among these, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant that can improve the charge / discharge performance of a battery and a low-viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred. In this case, the performance of the electrolyte may be excellent if the cyclic carbonate and the chain carbonate are mixed at a volume ratio of about 1:1 to about 1:9.

[0108] The lithium salt may be used without any particular limitation as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. 6 , LiClO 4 , LiAsF 6 , LiBF 4 , LiSbF 6 , LiAlO 4 , LiAlCl 4 , LiCF 3 SO 3 , LiC 4 F 9 SO 3 , LiN(C 2 F 5 SO 3 ), LiN(C 2 F 5 SO 2 ) 2 , LiN(CF 3 SO 2 ) 2 , LiCl, LiI, or LiB(C 2 O 4 ) 2 The lithium salt may be used at a concentration within the range of 0.1 to 2.0 M. When the lithium salt concentration is within this range, the electrolyte has appropriate conductivity and viscosity, and therefore excellent electrolyte performance can be exhibited, and lithium ions can migrate effectively.

[0109] When the electrolyte used in the present application is a solid electrolyte, for example, a solid inorganic electrolyte such as a sulfide-based solid electrolyte, an oxide-based solid electrolyte, a nitride-based solid electrolyte, or a halide-based solid electrolyte may be used, and preferably, a sulfide-based solid electrolyte may be used.

[0110] As the material of the sulfide-based solid electrolyte, a solid electrolyte containing Li, an X element (wherein X is at least one selected from P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In) and S may be used. Examples of the sulfide-based solid electrolyte material include Li 2 SP2 S 5 , Li 2 SP 2 S-LiX (where X is a halogen element such as I or Cl), Li 2 SP 2 S 5 -Li 2 O, Li 2 SP 2 S 5 -Li 2 O-LiI, Li 2 S-SiS 2 , Li 2 S-SiS 2 - LiI, Li 2 S-SiS 2 -LiBr, Li 2 S-SiS 2 -LiCl, Li 2 S-SiS 2 -B 2 S 3 - LiI, Li 2 S-SiS 2 -P 2 S5-LiI, Li 2 S.B. 2 S 3 , Li 2 SP 2 S 5 -ZmSn (where m and n are integers and Z is Ge, Zn or Ga), Li 2 S-GeS 2 , Li 2 S-SiS 2 -Li 3 PO 4 , Li 2 S-SiS 2 -Li p MO q (where p, q are integers and M is P, Si, Ge, B, Al, Ga or In).

[0111] The solid electrolyte, preferably the sulfide-based solid electrolyte, may be amorphous or crystalline, or may be in a mixed amorphous and crystalline state.

[0112] As a material for oxide-based solid electrolytes, Li7 La 3 Zr 2 O 12 , Li 7-x La 3 Zr 1-x Nb x O 12 , Li 7-3x La 3 Zr 2 Al x O 12 , Li 3x La 2 / 3-x TiO 3 , Li 1+x Al x Ti 2-x (PO 4 ) 3 , Li 1+x Al x Ge 2-x (PO 4 ) 3 , Li 3 PO 4 , Li 3+x PO 4-x N x (LiPON), Li 2+2x Zinc 1-x GeO 4 (LISICON), etc.

[0113] The solid electrolyte may be disposed as a separate layer (solid electrolyte layer) between the positive electrode and the negative electrode. The solid electrolyte may be partially included in the positive electrode active material layer of the positive electrode, independent of the solid electrolyte layer, or the solid electrolyte may be partially included in the negative electrode active material layer of the negative electrode, independent of the solid electrolyte layer.

[0114] In addition to the electrolyte components, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing the decrease in battery capacity, improving the discharge capacity of the battery, etc. In this case, the additives may be contained in an amount of 0.1 to 5 wt% based on the total weight of the electrolyte.

[0115] As described above, the lithium secondary battery including the positive electrode active material according to the present invention stably exhibits excellent discharge capacity, output characteristics and life characteristics, and is therefore useful in the fields of portable devices such as mobile phones, notebook computers, and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs).

[0116] The external shape of the lithium secondary battery according to the present invention is not particularly limited, and may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, etc. Furthermore, the lithium secondary battery can be used not only as a battery cell used as a power source for a small device, but also preferably as a unit battery for a medium- to large-sized battery module including a plurality of battery cells.

[0117] According to yet another aspect of the present invention, there may be provided a battery module including the lithium secondary battery as a unit cell and / or a battery pack including the same.

[0118] The battery module or the battery pack can be used as a power source for one or more medium- to large-sized devices, such as a power tool, an electric vehicle (Electric Vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV), or a power storage system.

[0119] The present invention will be described in more detail below with reference to examples. However, these examples are for the purpose of illustrating the present invention, and the scope of the present invention is not to be construed as being limited by these examples.

[0120] The positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and may be, for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The positive electrode current collector may usually have a thickness of 3 to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesive strength of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0121] The positive electrode active material layer may be prepared by coating a positive electrode slurry composition containing the positive electrode active material, a conductive material, and optionally a binder, on the positive electrode current collector.

[0122] At this time, the positive electrode active material may be included in a content of 80 wt% to 99 wt%, more specifically, 85 wt% to 98.5 wt%, based on the total weight of the positive electrode active material layer, and excellent capacity characteristics can be exhibited when the content is within this range, but is not necessarily limited thereto.

[0123] The conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it has electronic conductivity without causing chemical changes in the battery that is constructed. Specific examples include graphite such as natural graphite and artificial graphite, carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, carbon-based materials such as carbon fibers, metal powders or metal fibers such as copper, nickel, aluminum, and silver, conductive whiskers such as zinc oxide and potassium titanate, conductive metal oxides such as titanium oxide, and conductive polymers such as polyphenylene derivatives, and the like, and one or more of these may be used alone or in combination. The conductive material may be contained in an amount of 0.1 wt% to 15 wt% based on the total weight of the positive electrode active material layer.

[0124] The binder serves to improve the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, and various copolymers thereof, and among these, one type alone or a mixture of two or more types may be used. The binder may be included in an amount of 0.1 to 15 wt% based on the total weight of the positive electrode active material layer.

[0125] The positive electrode may be manufactured by a typical method for manufacturing a positive electrode, except for using the positive electrode active material. Specifically, the positive electrode may be manufactured by dissolving or dispersing the positive electrode active material and, optionally, a binder and a conductive material in a solvent to prepare a positive electrode slurry composition, which is then coated on a positive electrode current collector, followed by drying and rolling.

[0126] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and one or more of these may be used alone or in combination. The amount of the solvent used is sufficient to dissolve or disperse the positive electrode active material, conductive material, and binder, and to provide a viscosity that allows excellent thickness uniformity when applied to manufacture a positive electrode, taking into consideration the coating thickness of the slurry and the production yield.

[0127] In another embodiment, the positive electrode may be manufactured by casting the positive electrode slurry composition on a separate support, peeling the positive electrode slurry composition from the support, and laminating the resulting film on a positive electrode current collector.

[0128] According to yet another aspect of the present invention, there may be provided an electrochemical device including the above-mentioned positive electrode. The electrochemical device may be, for example, a battery or a capacitor, and more specifically, a lithium secondary battery.

[0129] Specifically, the lithium secondary battery may include a positive electrode, a negative electrode facing the positive electrode, and a separator and an electrolyte interposed between the positive electrode and the negative electrode. Here, since the positive electrode is as described above, a detailed description thereof will be omitted for convenience, and only the remaining components not described above will be described in detail below.

[0130] The lithium secondary battery may optionally further include a battery container that houses an electrode assembly of the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container. The negative electrode may include a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0131] The negative electrode current collector is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may generally have a thickness of 3 μm to 500 μm, and like the positive electrode current collector, the surface of the current collector may be formed with fine irregularities to strengthen the binding force of the negative electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, or nonwoven fabric.

[0132] The negative electrode active material layer may be prepared by coating a negative electrode slurry composition containing the negative electrode active material, a conductive material, and optionally a binder, on the negative electrode current collector.

[0133] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon, metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys, and SiO β (0<β<2), SnO 2, a metal oxide capable of doping and dedoping lithium, such as vanadium oxide or lithium vanadium oxide, or a composite containing the metallic compound and a carbonaceous material, such as a Si-C composite or a Sn-C composite, may be used. Any one or a mixture of two or more of these may be used. A thin film of metallic lithium may be used as the negative electrode active material. In addition, both low-crystalline carbon and high-crystalline carbon may be used as the carbon material. Representative examples of low-crystalline carbon include soft carbon and hard carbon, and representative examples of high-crystalline carbon include amorphous, plate-like, scaly, spherical or fibrous natural graphite or artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, carbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes. The negative electrode active material may be included in an amount of 80 wt % to 99 wt % based on the total weight of the negative electrode active material layer.

[0134] The binder is a component that aids in bonding between the conductive material, the active material, and the current collector, and may be added in an amount of 0.1 wt% to 10 wt% based on the total weight of the negative electrode active material layer. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile-butadiene rubber, fluororubber, and various copolymers thereof.

[0135] The conductive material may be added as a component for further improving the conductivity of the negative electrode active material in an amount of 10 wt% or less, preferably 5 wt% or less, based on the total weight of the negative electrode active material layer. Such a conductive material is not particularly limited as long as it has conductivity without inducing a chemical change in the battery, and may be, for example, graphite such as natural graphite or artificial graphite, carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, or thermal black, conductive fibers such as carbon fibers or metal fibers, metal powders such as carbon fluoride, aluminum, or nickel powder, conductive whiskers such as zinc oxide or potassium titanate, conductive metal oxides such as titanium oxide, or conductive materials such as polyphenylene derivatives.

[0136] In one embodiment, the negative electrode active material layer may be prepared by coating a negative electrode slurry composition prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent on a negative electrode current collector and drying the coating. Alternatively, the negative electrode slurry composition may be cast on a separate support, and then peeled off from the support to obtain a film, which may be laminated on the negative electrode current collector.

[0137] In another embodiment, the negative electrode active material layer may be manufactured by coating a negative electrode slurry composition prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent on a negative electrode current collector and drying the coating, or by casting the negative electrode slurry composition on a separate support and peeling the composition from the support to obtain a film, which may be laminated on the negative electrode current collector.

[0138] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode to provide a path for lithium ions to move. Any separator that is generally used as a separator in a lithium secondary battery may be used without any particular limitation. In particular, it is preferable that the separator has low resistance to ion movement of the electrolyte and has excellent electrolyte humidification ability. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting point glass fiber, polyethylene terephthalate fiber, etc. may be used. In addition, in order to ensure heat resistance or mechanical strength, a coated separator containing a ceramic component or a polymer material may be used, and may be selectively used as a single layer or multilayer structure.

[0139] In addition, examples of the electrolyte used in the present application include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the production of lithium secondary batteries, but are not limited to these. Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0140] The organic solvent may be used without any particular limitation as long as it serves as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent may be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, or ε-caprolactone, an ether solvent such as dibutyl ether or tetrahydrofuran, a ketone solvent such as cyclohexanone, an aromatic hydrocarbon solvent such as benzene or fluorobenzene, dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), or propylene carbonate (propylene carbonate). Examples of the solvents that may be used include carbonate-based solvents such as ethylene carbonate (PC), alcohol-based solvents such as ethyl alcohol and isopropyl alcohol, nitriles such as R-CN (R is a straight-chain, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, and sulfolanes. Among these, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant that can improve the charge / discharge performance of a battery and a low-viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred. In this case, the performance of the electrolyte may be excellent if the cyclic carbonate and the chain carbonate are mixed at a volume ratio of about 1:1 to about 1:9.

[0141] The lithium salt may be used without any particular limitation as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. 6 , LiClO 4 , LiAsF 6 , LiBF 4 , LiSbF 6 , LiAlO 4 , LiAlCl 4 , LiCF 3 SO 3 , LiC 4 F 9 SO 3 , LiN(C 2 F 5 SO 3 ), LiN(C 2 F 5 SO 2 ) 2 , LiN(CF 3 SO 2 ) 2 , LiCl, LiI, or LiB(C 2 O 4 ) 2 The lithium salt may be used at a concentration within the range of 0.1 to 2.0 M. When the lithium salt concentration is within this range, the electrolyte has appropriate conductivity and viscosity, and therefore excellent electrolyte performance can be exhibited, and lithium ions can migrate effectively.

[0142] When the electrolyte used in the present application is a solid electrolyte, for example, a solid inorganic electrolyte such as a sulfide-based solid electrolyte, an oxide-based solid electrolyte, a nitride-based solid electrolyte, or a halide-based solid electrolyte may be used, and preferably, a sulfide-based solid electrolyte may be used.

[0143] As the material of the sulfide-based solid electrolyte, a solid electrolyte containing Li, an X element (wherein X is at least one selected from P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In) and S may be used. Examples of the sulfide-based solid electrolyte material include Li 2 SP2 S 5 , Li 2 SP 2 S-LiX (where X is a halogen element such as I or Cl), Li 2 SP 2 S 5 -Li 2 O, Li 2 SP 2 S 5 -Li 2 O-LiI, Li 2 S-SiS 2 , Li 2 S-SiS 2 - LiI, Li 2 S-SiS 2 -LiBr, Li 2 S-SiS 2 -LiCl, Li 2 S-SiS 2 -B 2 S 3 - LiI, Li 2 S-SiS 2 -P 2 S5-LiI, Li 2 S.B. 2 S 3 , Li 2 SP 2 S 5 -ZmSn (where m and n are integers and Z is Ge, Zn or Ga), Li 2 S-GeS 2 , Li 2 S-SiS 2 -Li 3 PO 4 , Li 2 S-SiS 2 -Li p MO q (where p, q are integers and M is P, Si, Ge, B, Al, Ga or In). The solid electrolyte, preferably the sulfide-based solid electrolyte, may be amorphous or crystalline, or may be in a mixed amorphous and crystalline state.

[0144] As a material for oxide-based solid electrolytes, Li 7 La 3 Zr2 O 12 , Li 7-x La 3 Zr 1-x Nb x O 12 , Li 7-3x La 3 Zr 2 Al x O 12 , Li 3x La 2 / 3-x TiO 3 , Li 1+x Al x Ti 2-x (PO 4 ) 3 , Li 1+x Al x Ge 2-x (PO 4 ) 3 , Li 3 PO 4 , Li 3+x PO 4-x N x (LiPON), Li 2+2x Zinc 1-x GeO 4 (LISICON), etc.

[0145] The solid electrolyte may be disposed as a separate layer (solid electrolyte layer) between the positive electrode and the negative electrode. The solid electrolyte may be included in a portion of the positive electrode active material layer of the positive electrode, independent of the solid electrolyte layer, or the solid electrolyte may be included in a portion of the negative electrode active material layer of the negative electrode, independent of the solid electrolyte layer.

[0146] In addition to the electrolyte components, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing the decrease in battery capacity, improving the discharge capacity of the battery, etc. In this case, the additives may be contained in an amount of 0.1 to 5 wt% based on the total weight of the electrolyte.

[0147] As described above, the lithium secondary battery including the positive electrode active material according to the present invention stably exhibits excellent discharge capacity, output characteristics and life characteristics, and is therefore useful in the fields of portable devices such as mobile phones, notebook computers, and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs).

[0148] The external shape of the lithium secondary battery according to the present invention is not particularly limited, and may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, etc. Furthermore, the lithium secondary battery can be used not only as a battery cell used as a power source for a small device, but also preferably as a unit battery for a medium- to large-sized battery module including a plurality of battery cells.

[0149] According to yet another aspect of the present invention, there may be provided a battery module including the lithium secondary battery as a unit cell and / or a battery pack including the same.

[0150] The battery module or the battery pack can be used as a power source for one or more medium- to large-sized devices, such as a power tool, an electric vehicle (Electric Vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV), or a power storage system.

[0151] The present invention will be described in more detail below with reference to examples. However, these examples are for the purpose of illustrating the present invention, and the scope of the present invention is not to be construed as being limited by these examples.

[0152] Production Example 1. Production of positive electrode active material Example 1 The lithium composite oxide NiCoMn(OH) was prepared by a known co-precipitation method using nickel sulfate, cobalt sulfate, and manganese sulfate. 2 A hydroxide precursor (Ni:Co:Mn=95:4:1 (at%)) was synthesized. The average particle size (D 50 ) was 3.0 μm.

[0153] Next, the first hydroxide precursor and LiOH (Li / (Ni+Co+Mn) molar ratio=1.05) were mixed, and then O 2 The mixture was then heat-treated (primary baking) at 790°C for 12 hours in a sintered atmosphere to obtain a lithium composite oxide. 3 and 0.1 mol% ZrO as a metal oxide dopant. 2 was introduced.

[0154] After the primary firing was completed, the lithium composite oxide was added to distilled water, stirred for 1 hour, and dried in a vacuum dryer at 120° C. for 12 hours.

[0155] Next, O 2The mixture was then subjected to a heat treatment (secondary baking) at 700° C. in a nitrogen atmosphere for 12 hours to obtain a positive electrode active material containing a lithium composite oxide.

[0156] Example 2 The lithium composite oxide NiCoMn(OH) was prepared by a known co-precipitation method using nickel sulfate, cobalt sulfate, and manganese sulfate. 2 A hydroxide precursor (Ni:Co:Mn=95:4:1 (at%)) was synthesized. The average particle size (D 50 ) was 3.0 μm.

[0157] Next, the first hydroxide precursor and LiOH (Li / (Ni+Co+Mn) molar ratio=1.05) were mixed, and then O 2 The mixture was then heat-treated (primary baking) at 790°C for 12 hours in a sintered atmosphere to obtain a lithium composite oxide. 3 and 0.1 mol% ZrO as a metal oxide dopant. 2 was introduced.

[0158] After the primary firing was completed, the lithium composite oxide was added to distilled water, stirred for 1 hour, and dried in a vacuum dryer at 120° C. for 12 hours.

[0159] Next, O 2 The mixture was then subjected to a heat treatment (secondary baking) at 700° C. in a nitrogen atmosphere for 12 hours to obtain a positive electrode active material containing a lithium composite oxide.

[0160] Example 3 The lithium composite oxide NiCoMn(OH) was prepared by a known co-precipitation method using nickel sulfate, cobalt sulfate, and manganese sulfate. 2 A hydroxide precursor (Ni:Co:Mn=95:4:1 (at%)) was synthesized. The average particle size (D 50 ) was 3.0 μm.

[0161] Next, the first hydroxide precursor and LiOH (Li / (Ni+Co+Mn) molar ratio=1.05) were mixed, and then O 2 The mixture was then heat-treated (primary baking) at 790°C for 12 hours in a sintered atmosphere to obtain a lithium composite oxide. 3 and 0.1 mol% ZrO as a metal oxide dopant. 2 was introduced.

[0162] After the primary firing was completed, the lithium composite oxide was added to distilled water, stirred for 1 hour, and dried in a vacuum dryer at 120° C. for 12 hours.

[0163] Next, O 2 The mixture was then subjected to a heat treatment (secondary baking) at 700° C. in a nitrogen atmosphere for 12 hours to obtain a positive electrode active material containing a lithium composite oxide.

[0164] Example 4 The lithium composite oxide NiCoMn(OH) was prepared by a known co-precipitation method using nickel sulfate, cobalt sulfate, and manganese sulfate. 2 A hydroxide precursor (Ni:Co:Mn=95:4:1 (at%)) was synthesized. The average particle size (D 50 ) was 3.0 μm.

[0165] Next, the first hydroxide precursor and LiOH (Li / (Ni+Co+Mn) molar ratio=1.05) were mixed, and then O 2 The mixture was then heat-treated (primary baking) at 790°C for 12 hours in a sintered atmosphere to obtain a lithium composite oxide. 3 and 0.1 mol% ZrO as a metal oxide dopant. 2 was introduced.

[0166] After the primary firing was completed, the lithium composite oxide was added to distilled water, stirred for 1 hour, and dried in a vacuum dryer at 120° C. for 12 hours.

[0167] Next, O 2 The mixture was then subjected to a heat treatment (secondary baking) at 700° C. in a nitrogen atmosphere for 12 hours to obtain a positive electrode active material containing a lithium composite oxide.

[0168] Comparative Example 1 The lithium composite oxide NiCoMn(OH) was prepared by a known co-precipitation method using nickel sulfate, cobalt sulfate, and manganese sulfate. 2 A hydroxide precursor (Ni:Co:Mn=95:4:1 (at%)) was synthesized. The average particle size (D 50 ) was 3.0 μm.

[0169] Next, the first hydroxide precursor and LiOH (Li / (Ni+Co+Mn) molar ratio=1.05) were mixed, and then O 2 The mixture was then heat-treated (primary baking) at 790°C for 12 hours in a sintered atmosphere to obtain a lithium composite oxide. 3 and 0.1 mol% ZrO as a metal oxide dopant. 2 was introduced.

[0170] After the primary firing was completed, the lithium composite oxide was added to distilled water, stirred for 1 hour, and dried in a vacuum dryer at 120° C. for 12 hours.

[0171] Next, O 2 The mixture was then subjected to a heat treatment (secondary baking) at 700° C. in a nitrogen atmosphere for 12 hours to obtain a positive electrode active material containing a lithium composite oxide.

[0172] Comparative Example 2 The lithium composite oxide NiCoMn(OH) was prepared by a known co-precipitation method using nickel sulfate, cobalt sulfate, and manganese sulfate. 2 A hydroxide precursor (Ni:Co:Mn=95:4:1 (at%)) was synthesized. The average particle size (D 50) was 3.0 μm.

[0173] Next, the first hydroxide precursor and LiOH (Li / (Ni+Co+Mn) molar ratio=1.05) were mixed, and then O 2 The mixture was then heat-treated (primary baking) at 790°C for 12 hours in a sintered atmosphere to obtain a lithium composite oxide. 3 was introduced.

[0174] After the primary firing was completed, the lithium composite oxide was added to distilled water, stirred for 1 hour, and dried in a vacuum dryer at 120° C. for 12 hours.

[0175] Next, O 2 The mixture was then subjected to a heat treatment (secondary baking) at 700° C. in a nitrogen atmosphere for 12 hours to obtain a positive electrode active material containing a lithium composite oxide.

[0176] Comparative Example 3 The lithium composite oxide NiCoMn(OH) was prepared by a known co-precipitation method using nickel sulfate, cobalt sulfate, and manganese sulfate. 2 A hydroxide precursor (Ni:Co:Mn=91:8:1 (at%)) was synthesized. The average particle size (D 50 ) was 3.0 μm.

[0177] Next, the first hydroxide precursor and LiOH (Li / (Ni+Co+Mn) molar ratio=1.05) were mixed, and then O 2 The mixture was then heat-treated (primary firing) at 790° C. in a 100% atmosphere for 12 hours to obtain a lithium composite oxide. 2 was introduced.

[0178] After the primary firing was completed, the lithium composite oxide was added to distilled water, stirred for 1 hour, and dried in a vacuum dryer at 120° C. for 12 hours.

[0179] Next, O2 The mixture was then subjected to a heat treatment (secondary baking) at 700° C. in a nitrogen atmosphere for 12 hours to obtain a positive electrode active material containing a lithium composite oxide.

[0180] Comparative Example 4 The lithium composite oxide NiCoMn(OH) was prepared by a known co-precipitation method using nickel sulfate, cobalt sulfate, and manganese sulfate. 2 A hydroxide precursor (Ni:Co:Mn=95:4:1 (at%)) was synthesized. The average particle size (D 50 ) was 3.0 μm.

[0181] Next, the first hydroxide precursor and LiOH (Li / (Ni+Co+Mn) molar ratio=1.05) were mixed, and then O 2 The mixture was then heat-treated (primary baking) at 790°C for 12 hours in a sintered atmosphere to obtain a lithium composite oxide. 3 and 0.1 mol% ZrO as a metal oxide dopant. 2 was introduced.

[0182] After the primary firing was completed, the lithium composite oxide was added to distilled water, stirred for 1 hour, and dried in a vacuum dryer at 120° C. for 12 hours.

[0183] Next, O 2 The mixture was then subjected to a heat treatment (secondary baking) at 700° C. in a nitrogen atmosphere for 12 hours to obtain a positive electrode active material containing a lithium composite oxide.

[0184] Manufacturing example 2. Manufacturing of lithium secondary battery (half cell) A positive electrode slurry was prepared by dispersing 94 wt% of the positive electrode active material prepared in Preparation Example 1, 3 wt% of carbon black, and 3 wt% of PVDF binder in 30 g of N-methyl-2-pyrrolidone (NMP). The positive electrode slurry was uniformly applied to a thin aluminum film having a thickness of 15 μm and dried in a vacuum at 135° C. to prepare a positive electrode for a lithium secondary battery.

[0185] A lithium foil was used as the counter electrode for the positive electrode, a porous polyethylene film (Celgard 2300, thickness: 25 μm) was used as the separator, and LiPF was dissolved in a solvent containing ethylene carbonate and ethyl methyl carbonate in a volume ratio of 3:7. 6 A half-cell was fabricated using an electrolyte in which Zn was present at a concentration of 1.15M.

[0186] Experimental Example 1. Analysis of particle size distribution of positive electrode active material The particle size distribution of the lithium composite oxide in each of the positive electrode active materials prepared in Preparation Example 1 was analyzed using a known laser diffraction method. Specifically, each positive electrode active material was dispersed in a dispersion medium, and then ultrasonic waves of about 28 kHz were irradiated at an output of 60 W using a laser diffraction particle size measuring device (Microtrac MT 3000), and a volume cumulative particle size distribution graph was obtained.

[0187] Next, the particle sizes corresponding to 10%, 50%, and 90% of the volume cumulative amount are determined from the volume cumulative particle size distribution graph (D 10 , D 50 , D 90 ), the minimum particle size (D min ) and the maximum particle size (D max ) was calculated. The analysis results are shown in Tables 1 and 2 below.

[0188] [Table 1]

[0189] [Table 2]

[0190] Experimental Example 2: Evaluation of the electrochemical characteristics of a lithium secondary battery (half cell) The lithium secondary battery (half cell) prepared in Preparation Example 2 was subjected to a charge-discharge experiment at 25° C., voltage range of 3.0V to 4.3V, and discharge rate of 1.0C / 0.1C using an electrochemical analyzer (Toyo, Toscat-3100) to measure initial charge capacity, initial discharge capacity, initial efficiency, and 1.0C / 0.1C rate characteristics.

[0191] In addition, the same lithium secondary battery (half cell) was charged and discharged 50 times at 45°C, voltage range of 3.0V to 4.3V, and 1C / 1C using an electrochemical analyzer (Toyo, Toscat-3100), and the ratio of the discharge capacity at the 50th cycle to the initial capacity (cycle capacity retention) was measured. The measurement results are shown in Table 3 below.

[0192] [Table 3]

[0193] Referring to the results in Table 3, it can be seen that the electrochemical characteristics of the lithium secondary batteries using the positive electrode active materials according to Examples 1 to 4, which have uniform particle size distribution and high sharpness of particle size distribution, are improved. In particular, it can be seen that the life characteristics related to the stability of the lithium secondary batteries using the positive electrode active materials according to Examples 1 to 4 are improved.

[0194] Although the embodiments of the present invention have been described above, a person having ordinary knowledge in the art may modify and change the present invention in various ways by adding, changing, deleting or adding elements without departing from the concept of the present invention described in the claims, and this may also be considered to be within the scope of the claims of the present invention.

Claims

1. A lithium composite oxide capable of lithium intercalation / deintercalation, The lithium composite oxide contains at least lithium and a transition metal, The lithium composite oxide is D 10 and D. 50 and D. 90 and D. max A positive electrode active material that satisfies all of the following formulas 1 to 3. [Formula 1] D 90 / D 10 ≦3.62 [Formula 2] D max -D 90 <2.0μm [Formula 3] D max / D min <5.19 (In the above formulas 1 to 3, the D 10 is a particle size of the lithium composite oxide at which the volume cumulative amount is 10% in a volume cumulative particle size distribution graph obtained by laser diffraction particle size distribution measurement, and 50 is the particle size of the lithium composite oxide at which the volume cumulative amount is 50% in the volume cumulative particle size distribution graph, and D 90 is the particle size of the lithium composite oxide at which the volume cumulative amount is 90% in the volume cumulative particle size distribution graph, and D min is the minimum particle size of the lithium composite oxide in the volume cumulative particle size distribution graph, and D max is the maximum particle size of the lithium composite oxide in the volume cumulative particle size distribution graph.

2. The lithium composite oxide is 50 The positive electrode active material according to claim 1, wherein the thickness of the positive electrode active material is 2 μm to 8 μm.

3. The lithium composite oxide is max The positive electrode active material according to claim 1 , wherein the thickness of the first and second electrodes is 15 μm or less.

4. The lithium composite oxide is 10 and the above D 50 and satisfy the following formula 4. The positive electrode active material according to claim 1 : [Formula 4] D 50 / D 10 <1.19

5. The lithium composite oxide is 50 and the above D max and satisfy the following formula 5. The positive electrode active material according to claim 1 : [Formula 5] D max -D 50 <7.8μm

6. 2. The positive electrode active material according to claim 1, wherein the transition metal is at least one selected from the group consisting of nickel, cobalt, manganese, and aluminum.

7. The positive electrode active material according to claim 1 , wherein the lithium composite oxide is represented by the following chemical formula 1: [Chemical formula 1] Li a Ni 1-(b+c+d) Co b M1 c M2 d O 2 (where: M1 is at least one selected from Mn and Al; M2 is at least one selected from the group consisting of Na, K, Mg, Ca, Ba, Mn, B, Ce, Hf, Ta, Cr, F, Al, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, Ge, Nd, Gd and Cu; M1 and M2 are different from each other, 0.5≦a≦1.5, 0≦b≦0.20, 0≦c≦0.30, 0≦d≦0.10.)

8. The positive electrode active material according to claim 1 , wherein in the above Chemical Formula 1, b+c+d is 0.30 or less.

9. The positive electrode active material according to claim 1 , wherein the lithium composite oxide is present in at least one form selected from a single particle and a secondary particle formed by aggregation of a plurality of primary particles.

10. The positive electrode active material according to claim 9, wherein the secondary particles are in a state where 2 to 10 primary particles are aggregated.

11. A positive electrode comprising the positive electrode active material according to claim 1 .

12. A lithium secondary battery using the positive electrode according to claim 11.

Citation Information

Patent Citations

  • Positive electrode active material for nonaqueous secondary battery and nonaqueous electrolyte secondary battery using positive electrode active material

    JP2013229339A

  • Positive electrode active material for nonaqueous electrolyte secondary battery

    JP2017188445A

  • Method for producing positive electrode active material for secondary battery

    JP2021516425A

  • Unwinding apparutus for being used in manufacturing electrode of secondary battery

    KR102594981B1